La Krisis della psichiatria e la sua riedificazione come scienza dell’uomo: La Daseinsanalyse di Ludwig Binswanger - Sganga, Michela (B@belonline, 2020)
The present contribution aims to investigate the genuine phenomenological attitude and approach that characterize the work of Ludwig Binswanger and his Daseinsanalyse – a method that the Swiss psychiatrist developed and improved through his entire life and medical experience. Starting from Husserl’s concept of Krisis – in Binswanger’s words, the spirit of separation typical of the modernity – it emerges the need to change, rethink and reorganize the entire epistemic setting of psychiatry. By doing so, Binswanger’s method leads to a new idea of medical science, in which all different knowledges can be used not only in order to identify symptoms, but also to understand why patients are suffering from them and how to better deal with them. Indeed, the focus of psychiatry cannot just be on the explanation of mental illness, but it has to embrace a wider comprehension of the person and his/her entire being. On this basis, Binswanger points out that psychiatry has a complex and multi-layered nature.